CCR6 defines a subset of activated memory T cells of Th17 potential in immune thrombocytopenia. (25th November 2018) - Lyu, M; Li, Y; Hao, Y; Lyu, C; Huang, Y; Sun, B; Li, H; Xue, F; Liu, X; Yang, R
Summary: Current researches have determined the significance of C-C chemokine receptor (CCR)6 expression as either a marker of T helper cells (Th) or an effector and regulator of T cell function. However, the roles of CCR6 in the pathogenesis of immune thrombocytopenia (ITP) are unclear. In this study, we aimed to investigate the phenotype and functional characteristics of circulating CCR6 + T cells in blood from chronic ITP patients and healthy controls. We found that the frequency of CCR6 + CD4 + cells was higher in ITP patients than in healthy controls. Anti-CD3/anti-CD28 stimulation induced rapid expansion of CCR6 + CD4 + cells in ITP patients. CCR6 + CD4 + cells had a phenotype of activated cells and predominantly expressed CD45RO. Forkhead box protein P3 (FoxP3) and CD25-positive cells were exclusively detected within the CCR6 + CD4 + cells. In ITP patients, CCR6 + regulatory T cells (Treg ) were decreased and positively correlated with platelet counts and transforming growth factor (TGF)-β plasma levels. In contrast to CCR6 – counterparts, CCR6 + CD4 + cells produced higher levels of interleukin (IL)-17A. The frequency of CCR6 + Th17 was higher in ITP patients and positively correlated with IL-17A levels in supernatant. Most importantly, CCR6 + CD4 + cell subpopulations, but not CCR6 − CD4 +, were closely correlated to treatment response of ITP patients. These findings suggest that circulating CCR6 + CD4 + cells in ITP patients have characteristics of activated memory Th17 phenotype and could be used to monitor disease activity and treatment response. Graphical Abstract: